ANALISIS KEPUASAN KARYAWAN DAN AKREDITASI RUMAH SAKIT UMUM DAERAH BLAMBANGAN KABUPATEN BANYUWANGI - Diansanto Prayoga; Syifaul Lailiyah; Jayanti Dian Eka Sari (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2017)
Health services conducted by hospitals must prioritize quality and satisfaction for consumers. Internal hospital customers are hospital works that have a major role in providing services to consumers. Analysis Methods This study uses Quantitative Descriptive Analysis method. For a large sample of staff employees taken 20% of all employees (589 people) at Blambangan Regional General Hospital Banyuwangi regency of 125 people by systematic random sampling. The results of this study indicate that the level of satisfaction of employee employee karywan for 68.95 included in the category of satisfaction. Hospital employee satisfaction value is the highest indicator of job satisfaction that is mentally challenging with the value of employee satisfaction of 71.72, while the lowest hospital employee satisfaction value is a reasonable indicator of Rewards satisfaction with employee satisfaction score of 64.23. Accreditation of Blambangan Public Hospital of Banyuwangi Regency earned the title of Plenary.This study reviews materials for the management of the hospital to make improvements in the role of hospital employees to perform services to the community and management evaluation in improving the performance of employees in the organization. Keyword : Job Satisfaction, Accreditation, Quality of Hospital